1980
DOI: 10.1104/pp.65.4.635
|View full text |Cite
|
Sign up to set email alerts
|

Soil Temperature Influences on Root Resistance of Pinus contorta Seedlings

Abstract: The influence of low temperature in the root zone on water uptake in lodgepole pine (Pinus contorta Dougl ex Loud.) was studied under laboratory conditions. To remove soil hydraulic influences, two-year-old seedlngs were transferred to solution cultures and maintained in temperature controlled water baths. Short term measurements of leaf conductance, leaf water potential and tritiated water movement were taken at root temperatures from 22 C down to 0 C. Root resistance was calculated to be 67% of total plant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 12 publications
6
73
0
Order By: Relevance
“…When measurements were made in June 2007 and 2008, white spruce needle gas exchange was constrained by cold soils (,7 uC), consistent with observations in the central Brooks Range (Goldstein et al, 1985). Cold soils are thought to reduce water flow into the roots by reducing membrane permeability and by increasing the viscosity of water (Kaufmann, 1975(Kaufmann, , 1977Running and Reid, 1980). Warm and dry conditions in mid-July 2007 led to drought-induced stomatal closure, particularly on shallow parent material, where trees draw water from either a smaller soil volume or a soil volume that is more subject to evaporative water loss.…”
Section: Constraints On Needle Gas Exchangesupporting
confidence: 66%
“…When measurements were made in June 2007 and 2008, white spruce needle gas exchange was constrained by cold soils (,7 uC), consistent with observations in the central Brooks Range (Goldstein et al, 1985). Cold soils are thought to reduce water flow into the roots by reducing membrane permeability and by increasing the viscosity of water (Kaufmann, 1975(Kaufmann, , 1977Running and Reid, 1980). Warm and dry conditions in mid-July 2007 led to drought-induced stomatal closure, particularly on shallow parent material, where trees draw water from either a smaller soil volume or a soil volume that is more subject to evaporative water loss.…”
Section: Constraints On Needle Gas Exchangesupporting
confidence: 66%
“…This photosynthetic dormancy during the cold season is consistent with earlier findings that root zone temperatures below 5 °C suppressed water uptake and stomatal conductance (Running and Reid, 1980;Jones, 1992). Daily GPP began to increase in early May as Ts increased rapidly from 0 to 10 °C.…”
Section: Gross Primary Productionsupporting
confidence: 91%
“…Leaf conductance during the summer increased dramatically to maximum values during mid-August at the same time warming soil temperatures at 25 cm approached 7" C. A similar value of near 7°C was found to be near a limiting threshold for root resistance to water uptake in P. engelmannii (Kaufmann 1975). Running and Reid (1980) also observed an approximate 7" C threshold for increased root conductance to water uptake in P. contorra seedlings. Recently, Teskey et al (1983) reported that cold root temperatures resulted in stomatal closure that was independent of leaf water potentiril in Abies umuhilis.…”
Section: Discussionmentioning
confidence: 64%
“…As indicated in Fig. 5, a similar reduction in soil water uptake by the roots may also occur when soil temperatures are low (Kaufmann 1975, Dalton and Gardner 1978, Running and Reid 1980, Teskey et al 1983). Other recent work has found a strong correlation between maximum daily leaf conductance and soil temperatures for A .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation